Regular aerobic exercise is positively associated with hippocampal structure and function in young and middle‐aged adults. Issue 3 (27th December 2021) - Hendrikse, Joshua; Chye, Yann; Thompson, Sarah; Rogasch, Nigel C.; Suo, Chao; Coxon, James P.; Yücel, Murat
Abstract: Regular exercise has numerous benefits for brain health, including the structure and function of the hippocampus. The hippocampus plays a critical role in memory function, and is altered in a number of psychiatric disorders associated with memory impairments (e.g., depression and schizophrenia), as well as healthy aging. While many studies have focused on how regular exercise may improve hippocampal integrity in older individuals, less is known about these effects in young to middle‐aged adults. Therefore, we assessed the associations of regular exercise and cardiorespiratory fitness with hippocampal structure and function in these age groups. We recruited 40 healthy young to middle‐aged adults, comprised of two groups (n = 20) who self‐reported either high or low levels of exercise, according to World Health Organization guidelines. We assessed cardiorespiratory fitness using a graded exercise test (VO2 max) and hippocampal structure via manual tracing of T1‐weighted magnetic resonance images. We also assessed hippocampal function using magnetic resonance spectroscopy to derive estimates of N ‐acetyl‐aspartate concentration and hippocampal‐dependent associative memory and pattern separation tasks. We observed evidence of increased N ‐acetyl‐aspartate concentration and associative memory performance in individuals engaging in high levels of exercise. However, no differences in hippocampal volume or pattern separation capacity were observed between groups. Cardiorespiratory fitness was positively associated with left and right hippocampal volume and N ‐acetyl‐aspartate concentration. However, no associations were observed between cardiorespiratory fitness and associative memory or pattern separation. Therefore, we provide evidence that higher levels of exercise and cardiorespiratory fitness are associated with improved hippocampal structure and function. Exercise may provide a low‐risk, effective method of improving hippocampal integrity in an early‐to‐mid‐life stage.